Adsorption of Cadmium(II) Ion from Aqueous Solutions onto Synthetic Terpolymer: Isotherm and Kinetic Study - Sangu, V.; Kannan, K.; Srinivasan, K. (Asian Journal of Chemistry, 2014)
The adsorption of cadmium(II) onto a terpolymer 4-HBTUPF synthesized by condensation of 4-hydroxybenzoic acid and thiourea with paraformaldehyde in 2:3:5 ratios. The effect of experimental parameters such as pH, metal ion concentration, contact time and adsorbents dosage on cadmium(II) removal were studied. The data were analyzed using Langmuir and Freundlich equations to describe the equilibrium isotherms. The kinetic data fitted well with pseudo second order model than with pseudo first order model. The maximum adsorption capacity for the adsorption of cadmium(II) on the 4-HBTUPF adsorbent calculated from Langmuir isotherm was found to be 44.64 mg/g for the adsorption of cadmium(II) on 4-HBTUPF terpolymer. R2 values shows that Langmuir model fit better than Freundlich model. FTIR analysis was used to obtain information on the nature of possible interaction between adsorbents and metal ions. SEM images confirmed the adsorption of cadmium onto the terpolymer through morphological observations. Thermodynamic study showed the feasibility of process and spontaneous nature of the adsorption. The results indicate that terpolymer 4-HBTUPF could be used effectively for the removal of cadmium from aqueous solution.